GEOGEBRA-ASSISTED LEARNING, DOING, AND REPEATING (LDR) MODEL TO DEVELOP COMMUNITY NUMERACY SKILLS - Delima, Nita; Supriyadi, Endang Irawan; Aminah, Mimin (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
In the Society 5.0 era, strong numeracy skills are essential for processing complex data and making informed decisions. However, the numeracy levels of the Indonesian population remain relatively low, underscoring the need for effective educational interventions. This study investigates the effectiveness of the Learning, Doing, and Repeating (LDR) model, supported by GeoGebra, in developing community-based numeracy skills. The LDR model structures learning through iterative cycles: initial instruction (Learning), direct application (Doing), and reinforcement (Repeating), with GeoGebra facilitating the visualization of mathematical relationships. An experimental one-group pretest–posttest design was employed, involving community members guided by PKBM Yapenmas. Numeracy skills were assessed using mathematics tasks adapted from the PISA 2022 framework, alongside observations and interviews. The results indicated significant improvements in participants' numeracy skills following the intervention. The use of GeoGebra was found to enhance participants' conceptual understanding and engagement during the learning process. These findings suggest that the LDR model, when integrated with interactive technology, offers an effective approach to fostering numeracy development in informal educational contexts. This study contributes to the growing field of technology-assisted mathematics education and highlights the potential of iterative learning models for strengthening foundational numeracy skills within community learning environments.